Fuzzy Robust Estimation For Location Parameter - Mohammed, Mohammed Jasim (Journal of Economics and Administrative Sciences, 2020)
In this paper, we introduce three robust fuzzy estimators of a location parameter based on Buckley’s approach, in the presence of outliers. These estimates were compared using the variance of fuzzy numbers criterion, all these estimates were best of Buckley’s estimate. of these, the fuzzy median was the best in the case of small and medium sample size, and in large sample size, the fuzzy trimmed mean was the best.